IHR-PVS national bridging workshop for Somalia: An interactive and participatory approach for operationalizing the One Health roadmap - Osman, A.Y.; Saidouni, A.; Wambua, Lillian; Mahrous, H.; Malik, S.M.M.R.; Lubogo, M.; Weerdt, R.V. de; Adam, A.H.; Mohamed, H.H.; Makhzoumi, K.A.; Ali, G.A.; Nur, M.O.; et al. (Elsevier, 2024)
Background: National Bridging Workshops (NBW) are a tool for reviewing collaboration gaps between line ministries relevant to the One Health framework.